The Landscapes of Full-Length Transcripts and Splice Isoforms as Well as Transposons Exonization in the Lepidopteran Model System, Bombyx mori - Dai, Zongrui; Ren, Jianyu; Tong, Xiaoling; Hu, Hai; Lu, Kunpeng; Dai, Fangyin; Han, Min-Jin (Frontiers in Genetics, 2021)
The domesticated silkworm, Bombyx mori, is an important model system for the order Lepidoptera. Currently, based on third-generation sequencing, the chromosome-level genome of Bombyx mori has been released. However, its transcripts were mainly assembled by using short reads of second-generation sequencing and expressed sequence tags (ESTs), which cannot explain the transcript profile accurately. Here, we used PacBio Iso-Seq technology to investigate the transcripts from 45 developmental stages of Bombyx mori. We obtained 25,970 non-redundant high-quality consensus isoforms capturing ~60% of previous reported RNAs, 15,431 (~47%) novel transcripts, and identified 7,253 long non-coding RNA (lncRNA) with a large proportion of novel lncRNA (~56%). In addition, we found that transposable elements (TEs) exonization account for 11,671 (~45%) transcripts including 5,980 protein-coding transcripts (~32%) and 5,691 lncRNAs (~79%). Overall, our results expand the silkworm transcripts and have general implications to understand the interaction between TEs and their host genes. These transcripts resource will promote functional studies of genes and lncRNAs as well as TEs in the silkworm.